Determinants of tax compliance among MSMEs in the food and beverage sector: The role of knowledge, awareness, and sanctions - Amalia, Arifa Rizky (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: Micro, Small, and Medium Enterprises (MSMEs) in Indonesia’s food and beverage sector often struggle with tax compliance, particularly regarding the 0.5% Final Income Tax (PPh Final). The complexity of tax regulations, limited knowledge, and negative perceptions contribute to low utilization of tax incentives and reduced compliance levels. Understanding the behavioral and structural factors that influence compliance is essential for developing effective tax policy interventions. Methods: The study employed a quantitative research method with a mixed-methods approach. It focused on analyzing the effects of three main variables—tax knowledge, taxpayer awareness, and tax sanctions—on MSME tax compliance. Data were collected from MSME taxpayers in Jakarta's food and beverage sector and analyzed using statistical techniques to assess both partial and simultaneous relationships. Findings: The findings reveal that tax knowledge has a significant positive effect on tax compliance. However, taxpayer awareness and tax sanctions individually do not significantly affect tax compliance. Simultaneously, tax knowledge, taxpayer awareness, and tax sanctions have a significant influence on tax compliance.  Conclusion: The study concludes that tax education is the most crucial factor in increasing MSME compliance. Simply raising awareness or imposing sanctions is insufficient without trust, understanding, and fair policy application. Policymakers are encouraged to expand tax education programs, improve communication with taxpayers, and ensure consistent enforcement. Novelty/Originality of this article: This research provides a nuanced view of tax compliance behavior among MSMEs by integrating psychological, legal, and educational perspectives. Furthermore, it proposes future exploration of social norms and taxpayer perceptions—an area often overlooked in quantitative compliance studies—making it a valuable contribution to the literature on behavioral public finance.